Dual-polarized angle-selective surface based on double-layer frequency selective surface - Du, Chao (2024)
In this Letter, we propose a dual-polarized angle-selective surface (ASS) based on a double-layer frequency selective surface (FSS) to achieve angular selectivity. By appropriately constructing the structure of the single-layer FSS, bandpass and band-stop are produced by the ASS under normal and oblique incidences, respectively, resulting in exceptional angular selectivity. Simulated results show that the proposed low-pass ASS achieves a bandpass (|S21| > −1 dB) from 0° to 10° and a band-stop (|S21| < −20 dB) from 31° to 85° with a profile thickness of 0.6 λ. A low-pass ASS prototype with an operating frequency of 10 GHz is fabricated to demonstrate the design concept. The measured results of the transmission coefficients are in good agreement with the simulated results. The proposed ASS can play an important role in many applications, as in minimizing the side lobes of the antenna.